HUBUNGAN STATUS GIZI, ASUPAN ZAT GIZI DAN AKTIVITAS FISIK DENGAN SIKLUS MENSTRUASI REMAJA PUTRI PONDOK PESANTREN SALAFIYAH KAUMAN KABUPATEN PEMALANG TAHUN 2016 - Nurul Hidayah; M. Zen Rahfiludin; Ronny Aruben (Jurnal Kesehatan Masyarakat (Undip), 2016)
The imbalance of nutritional status, nutrient intake, and the heavy physical activity will affect the reproduction function which causing the menstrual cycle disorder.  It indicates the ovulation problems or another medical condition. The objective of this study is to analyze the relationship between nutritional status, nutrient intake, and the heavy physical activity with the menstrual cycle of adolescent girls in Pondok Pesantren Salafiyah Kauman Pemalang.A quantitative method with a cross sectional approach was conducted in this study. The population of this study was the 130 adolescent girls in Pondok Pesantren Salafiyah Kauman Pemalang who have already menstruated. The sampling process was administered by applying a simple random sampling technique. The researcher took 108 Adolescent girls as the sample. The univariat analysis and bivariat analysis (chi square test) were conducted in this study. The result showed that 50 % of respondents have normal nutritional status, 69,4% of respondent have little intake of protein, 81,5% of respondents have little intake of fat,74,1 % of respondents have little intake of energy, 88,9 % of respondents have little intake of calcium, 84,3% of respondents have a light physical activity and 60,2 % of respondents have the irregularity menstrual cycle. Bivariat analysis indicates that there is a correlation(relationship)  between nutritional status and nutrition intake with the menstrual cycle (p<0,05). There is no correlation between physical activity with the menstrual cycle (p>0,05).There is correlation between nutrient intake with the physical activity.